Russian-Kalmyk Negotiations and the Shert’ of 1677 - Vladimir T. Tepkeev (Oriental Studies)
Introduction. The article discusses circumstances behind the Russian-Kalmyk negotiations and Shert’ (‘oath/treaty of allegiance’) of 1677. Goals. The study seeks to introduce some newly discovered sources dealing with seventeenth-century Kalmyk-Russian relations. Materials. The work focuses on Ambassadorial Book 5 contained in Collection 119 (‘Kalmyk Affairs’) of the Russian State Archive of Ancient Acts. Results. The Treaty of 1677 and related preceding arrangements were characterized by mutual suspicion and mistrust. The main Kalmyk-party guarantors — besides Ayuka proper —were Noyon Yeke-Zamsa of Torghuts and Tayiji Solom-Tseren of Dorbets. Conclusions. The Shert’ of 1677 would largely duplicate provisions of the 1673 one. However, it was supplemented with a few points, namely: 1) external political contacts of Kalmyk noblemen would be essentially limited, 2) all ethnic Russian captives of 1675–1677 were to be returned and offenders be punished, 3) diplomatic protocol and procedures to be henceforth followed by Ayuka with Russian Tsar’s ambassadors and written messages were articulated in greater detail.